COVID-19 myocardial pathology evaluation in athletes with cardiac magnetic resonance (COMPETE CMR) - Clark, D. E.; Parikh, A.; Dendy, J. M.; Diamond, A. B.; George-Durrett, K.; Fish, F. A.; Slaughter, J. C.; Fitch, W.; Hughes, S. G.; Soslow, J. H. (Circulation, 2020)
Myocarditis is a leading cause of sudden cardiac death among athletes and may occur without antecedent symptoms. COVID-19-related cardiac magnetic resonance (CMR) abnormalities have been described in 78% of mostly ambulatory adults, 1 creating concerns over COVID-19-related myocarditis in athletes. A report of 26 COVID-19+ collegiate athletes revealed late gadolinium enhancement (LGE) in 46%, with 4 (15%) meeting modified Lake Louise criteria for myocarditis.2, 3 However, without an athletic comparator group it is difficult to discern whether LGE represents healing myocarditis or athletic remodeling, as inferoseptal RV insertion LGE is common among athletes. We report the findings of a larger CMR study to evaluate the incidence and extent of cardiovascular pathology among COVID-19+ collegiate athletes, with comparison to athletic and healthy control groups.